2018
DOI: 10.1071/sr17304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating dispersive potential to identify the threshold electrolyte concentration in non-dispersive soils

Abstract: Use of non-traditional and marginal quality saline sodic water will increase in water limited environments and methods to assess use suitability are required. The threshold electrolyte concentration (CTH) defines the soil solution concentration, for a given soil solution sodicity, at which an acceptable reduction in the soil hydraulic conductivity (10–25%) is maintained without further soil structural degradation. The traditional method of determining CTH is via leaching columns, which are laborious and often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It indicates that the combination of solution salinity and the particular type and combination of cations is more important than simple NaCl salinity. These results are similar to those of Mosley et al (2017) and Dang et al (2018) where exact concentrations of individual electrolytes were difficult to establish.…”
Section: Discussionsupporting
confidence: 84%
“…It indicates that the combination of solution salinity and the particular type and combination of cations is more important than simple NaCl salinity. These results are similar to those of Mosley et al (2017) and Dang et al (2018) where exact concentrations of individual electrolytes were difficult to establish.…”
Section: Discussionsupporting
confidence: 84%
“…Abundant field and laboratory experiments have demonstrated that while moderately sodic conditions may cause small declines in K s via the temporary swelling of clay particles, more extreme inputs can cause an actual breakdown of the bonds between soil particles, leading to irreversible dispersal of clay particles and long‐term destruction of soil aggregates (Bhardwaj et al., 2008; Dang et al., 2018, 2018a, 2018b; Levy et al., 2005; McNeal et al., 1968; Menezes et al., 2014; Oster & Schroer, 1979; Shabtai et al., 2014). The exact thresholds at which this transition from reversible to irreversible damage occurs is highly soil specific, dependent on clay mineralogy, and other factors (Bennett et al., 2019; Dang et al., 2018, 2018a, 2018b; Frenkel et al., 1978; Levy et al., 2005; McNeal et al., 1968; Menezes et al., 2014; Quirk & Schofield, 1955; Y. Zhu et al., 2019). The USDA initially identified ESPs above 15 as dangerous for soils (McGeorge, 1954), while other experimental work has demonstrated that ESPs as low as five can cause serious soil damage (McIntyre, 1979; Oster & Schroer, 1979).…”
Section: Effects Of Salinity and Sodicity On Plants And Soilsmentioning
confidence: 99%
“…The effect of changing chemical conditions on soil structure can be analyzed through changes in saturated hydraulic conductivity, K s (mm/day). Abundant field and laboratory experiments have demonstrated that while moderately sodic conditions may cause small declines in K s via the temporary swelling of clay particles, more extreme inputs can cause an actual breakdown of the bonds between soil particles, leading to irreversible dispersal of clay particles and long-term destruction of soil aggregates (Bhardwaj et al, 2008;Dang et al, 2018Dang et al, , 2018aDang et al, , 2018bLevy et al, 2005;McNeal et al, 1968;Menezes et al, 2014;Oster & Schroer, 1979;Shabtai et al, 2014). The exact thresholds at which this transition from reversible to irreversible damage occurs is highly soil specific, dependent on clay mineralogy, and other factors (Bennett et al, 2019;Dang et al, 2018Dang et al, , 2018aDang et al, , 2018bFrenkel et al, 1978;Levy et al, 2005;McNeal et al, 1968;Menezes et al, 2014;Quirk & Schofield, 1955;Y.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 99%
“…The nonlinear inverse modeling included additional parameters, such as solution EC and soil clay content, which are critical governing factors in the management of the extent of K s reduction (Agassi et al, 1981;Cook et al, 2006;Dang et al, 2018aDang et al, , 2018cZhu et al, 2016). An increase in EC generates the osmotic pressure that compresses the diffuse double layer repulsive effect on the clay domains (Quirk, 2001), subsequently diminishing the contribution of pH and SAR on the diffuse double layer expansion (Sumner, 1993).…”
Section: Nonlinear Performance and Future Directionsmentioning
confidence: 99%